2015
DOI: 10.7717/peerj.1031
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the attitudes of medical faculty members and students in Pakistan towards plagiarism: a cross sectional survey

Abstract: Objective. The objective of this survey was to explore the attitudes towards plagiarism of faculty members and medical students in Pakistan.Methods. The Attitudes Toward Plagiarism questionnaire (ATP) was modified and distributed among 550 medical students and 130 faculty members in 7 medical colleges of Lahore and Rawalpindi. Data was entered in the SPSS v.20 and descriptive statistics were analyzed. The questionnaire was validated by principal axis factoring analysis.Results. Response rate was 93% and 73%, r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 17 publications
2
28
0
Order By: Relevance
“…These study findings were similar to the result obtained by Rathore et al [33] in their study conducted to explore the medical staff ATP in Pakistan. The study discovered that the majority of the studied subjects had moderate or high score of plagiarism attitude and the lower scores of their ATP were correlated with training sessions about scientific writing skills and research ethics.…”
Section: Discussionsupporting
confidence: 82%
“…These study findings were similar to the result obtained by Rathore et al [33] in their study conducted to explore the medical staff ATP in Pakistan. The study discovered that the majority of the studied subjects had moderate or high score of plagiarism attitude and the lower scores of their ATP were correlated with training sessions about scientific writing skills and research ethics.…”
Section: Discussionsupporting
confidence: 82%
“…7 Rathore et al reported positive attitudes of the medical students towards plagiarism in their study conducted in Lahore, Pakistan in 2015. 18 In this study, we found statistically significant differences between the attitudes and practices of medical and non-medical students towards plagiarism with a generally negative attitude among medical students towards the act of plagiarism, possibly as a result of greater experience in the field. Thus, significant emphasis was laid on the detailed discussion of plagiarism in research ethics.…”
Section: Discussionmentioning
confidence: 55%
“…Although the study included a relatively small number of participants, it points to knowledge gaps and attitudes that could affect the quality of scientific writing. The survey used an educative approach whereby participants learned definitions and aspects of referencing as they progressed in the survey, which is different from other previous used validated tools for evaluating attitudes towards plagiarism, both in high-income and low- and middle-income countries [ 14 – 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the field of correct referencing is not always a clear-cut matter of wrong and right, and also, academics may have different views on issues such as appropriate referencing, what is common knowledge, and self-plagiarism. Self-plagiarism is generally viewed as a lesser offense, especially when the views on plagiarism are lenient [ 14 ].…”
Section: Introductionmentioning
confidence: 99%